2014
DOI: 10.3144/expresspolymlett.2014.6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(ester amide) from remewable resources through melt polycondensation

Abstract: Abstract. Biodegradable poly(ester amide)s (PEAs) were synthesized from lactic acid and 11-aminoundecanoic acid via melt polycondensation. Molecular weights, chemical structures and thermal properties of the poly(ester amide)s were characterized in terms of gel permeation chromatography (GPC), Fourier transform infrared spectroscopy (FTIR), 1 H nuclear magnetic resonance ( 1 H NMR), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA), respectively. The PEAs have low molecular weights a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…The poly(ester amide)s showed two stage decomposition behavior in TG. Similar two step thermal degradation behaviors were observed for some reported poly(ester amide)s, where the first degradation step was assigned to the ester bond cleavage [34,49,50]. All the poly(ester amide)s showed higher T d5 values than that of PA4 [24] as indicated in Table 2.…”
Section: Discussionsupporting
confidence: 77%
“…The poly(ester amide)s showed two stage decomposition behavior in TG. Similar two step thermal degradation behaviors were observed for some reported poly(ester amide)s, where the first degradation step was assigned to the ester bond cleavage [34,49,50]. All the poly(ester amide)s showed higher T d5 values than that of PA4 [24] as indicated in Table 2.…”
Section: Discussionsupporting
confidence: 77%
“…For all BPEAs, the decomposition temperatures are considerably higher than the melting temperatures, which is important for the processing of these materials. From the TGA results, the thermal stability of poly(ester amide) is superior to that of polyester and comparable to previous poly(ester amide)s . As shown in Table , the thermal stability improves with the increase of DD content because of the increase of the number of amide units of BPEAs.…”
Section: Resultssupporting
confidence: 51%
“…The second decomposition step was very low for the PEA from succinic acid, but became more acute with the increase of carbon content in the PEA. According to literature [40,41], the first stage of decomposition was assigned to the cleavage of the ester bonds, and the second to one of the amide bonds. T. Fey et al [42] showed that the thermal degradation of PEA synthesized from succinic anhydride and amino alcohols (H 2 N-(CH 2 ) x -OH with x=2 to 6) resulted in the formation of Nhydroxyalkyl imides by a nucleophilic attack of the amide nitrogen to the neighboring ester carbonyl group through an intramolecular reaction.…”
Section: Thermal Propertiesmentioning
confidence: 99%